PENERAPAN ARTIFICIAL INTELLIGENCE, BIG DATA, DAN BLOCKCHAIN DALAM FINTECH PAYMENT TERHADAP RISIKO PENIPUAN KOMPUTER (COMPUTER FRAUD RISK): A SYSTEMATIC LITERATURE REVIEW - Caseba, Farah Labibah; Dewayanto, Totok (Diponegoro Journal of Accounting, 2024)
This research is aimed at finding out the benefits, driving factors and challenges of applying artificial intelligence, big data and blockchain to fintech payments in preventing the risk of computer fraud. This research uses the systematic literature review (SLR) method by analyzing articles obtained through literature selection related to the research objectives. Articles were obtained based on keywords, published in Scopus indexed academic journals published from 2020 to 2024, and other inclusion criteria in the research. This research uses twenty selected articles according to research criteria which will be analyzed further. The systematic literature review (SLR) method is used with the aim of collecting and evaluating related research systematically and avoiding subjective identification. This research found that the application of artificial intelligence, big data and blockchain in fintech payments can prevent the risk of computer fraud. The optimal combination of artificial intelligence, big data and blockchain technology provides many benefits and conveniences in fintech payments. However, it is necessary to consider the challenges and risks that arise as technology continues to develop. It is hoped that these findings will provide benefits for future researchers, companies in related fields, and fintech payment users in everyday life.